BUILT ENVIRONMENT FRACTALITY AS A CRITERION OF SPACE MANAGEMENT - Jevrić, Marija; Popkonstantinović, Branislav (Journal of Applied Engineering Science, 2014)
In accordance with the holographic paradigm of the universe, recent studies indicate the importance of fractality of the human environment for his mental and physical well-being. There was awareness of that in the past, but the conventional methods of planning cities have forgotten that. The lack of hierarchy and human scale in modern cities, as so as its geometrically regular shapes and flattened lines, are associated with some negative social phenomena. Therefore, this paper aims to highlight the importance of fractality of built environment and to suggest the possibilities of its use as a criterion of space management.